Congenital heart defects according to the types of the risk factors - a single center experience - Pavlicek, Jan; Klaskova, Eva; Prochazka, Martin; Dolezalkova, Erika; Matura, David; Spacek, Richard; Simetka, Ondrej; Gruszka, Tomas; Polanska, Slavka; Kacerovsky, Marian (Journal of maternal-fetal & neonatal medicine, 2019)
Objective: The main aim of this study was to compare the prevalence of congenital heart defects (CHDs) between pregnant women with and those without the risk factors. The secondary aim was to determine the influence of the specific risk factors, divided into subgroups, on the development of the CHD. Methods: The presented results were obtained over the course of a 15-year study between years 2002 and 2016. Fetal echocardiography was performed as a planned screening examination during the second trimester of gravidity. A total of 35,831 singleton pregnancies were examined at our center. Risk factors for the development of CHDs were analyzed and divide into the following groups: (i) maternal age ≥35 years; (ii) mother-related risk factors; (iii) pregnancy- and fetus-related risk factors; (iv) pregnancy after in vitro fertilization (IVF); (v) history of CHDs in the first-degree family member; (vi) history of CHDs in the second-degree family member; and (vii) positive genetic family history. Results: The risk factors were identified in 25% (8990/35,831) of pregnancies. In total, CHDs were detected in 1.1% (394/35,831) of fetuses. The prevalence rate of CHDs was higher in the pregnancies with than in those without the risk factors (2.5% [221/8990] versus 0.6% [173/26,841]; p < .0001). The presence of pregnancy- and fetus-related risk factors (odds ratio [OR], 6.5; 95% confidence interval [CI], 4.3-9.7) and pregnancy after IVF (OR, 2.8; 95% CI, 1.5-5.2) were found to be independent risk factors of CHDs. Conclusions: The presence of specific risk factors is related to the increasing prevalence of CHDs. Pregnancy- and fetus-related risk factors and in vitro fertilization were found to be the independent risk factors of CHD.
Keywords: dospělí; Female; Prevalence; novorozenec; Heart Defects, Congenital; Adult; ženské pohlaví; lidé; Infant, Newborn; těhotenství; kohortové studie; Risk Factors; prevalence; retrospektivní studie; Cohort Studies; Czech Republic; rizikové faktory; Česká republika; vrozené srdeční vady; Pregnancy; Retrospective Studies; Humans